Partial Severance: Distance Education and Parent Universities in Ghana - Tettey, Emmanuel; Arkor Tetteh, Abijah (MultiTech Publisher, 2024)
Distance Education has come to stay and it is very significant in the advancement of making education accessible to a broader popular. This distance education stems from a parent university, however, there seem to be a partial disconnection between the distance education and their parent university. The purpose of this study is there to explore the factors that account for the partial severance and the perceptions of distance education students regarding their sense of connection with the parent university. The qualitative research approach was adopted for the study. Consistent with the approach, case study design was used for the study. Purposive sampling technique was used to sample twenty-five (25) participants for the study, twelve (12) lecturers and thirteen (13) students. Interview guide was the research instrument used to collect data for the study. The thematic analysis was used to analyse the data. The study revealed that inadequate integration and communication between distance education students and the main campus significantly contribute to their sense of disconnection. Moreso, Distance Education students perceive their connection with the parent university as weak and insufficient due to feelings of isolation and exclusion from campus activities. They face significant communication gaps and lack access to resources and support services equivalent to those available to on-campus students. Based on the key findings, it is recommended that, parent universities who have established distance education should launch regular channels of communication to keep distance learners informed about campus events, resources, and opportunities for engagement. Also, parent universities must prioritize equitable access to resources and support services for distance education students. By creating a more inclusive and supportive environment, there will be a strong connection between parent universities and distance education, ultimately enriching their academic journey and overall satisfaction.